Revisión tratadística de las proporciones empleadas en la construcción de la estructura de la iglesia de San Juan bautista en Tiripetío, Michoacán, México. Comentarios a los resultados del análisis estructural a botareles de contrafuertes y su restauració - Bedolla-Arroyo, J. A.; Martínez-Molina, W.; Alonso-Guzmán, E. M.; Briansó-Penalva, J. L. (Revista ALCONPAT, 2012)
The Tiripetío building is emblematic. It is founded on a clay soil. It has undergone modifications due to structural, architectural, aesthetic and functional reasons. The construction of this temple dates back from the 16th century. It was built with stone masonry natural binder with clay and wood roof. The plant consists of a single rectangular bay of 12 m wide x 50 m in length, which includes 5 lateral buttresses, showing structural failure in the upper and lower ends. To analyze the root causes of the fractures, it was checked that the building was built according to the geometry described in various former treaties which would have a proper mechanical behavior. The main conclusions obtained from the structural analysis at botareles buttresses, as well as the study of soil mechanics, were that fractures present at the botareles of the buttresses are due to improper selection of the used natural masonry as well as an inappropriate construction procedure.Keywords: factory; treaties; historic buildings; buttresses; flying buttresses